Designing the Ideal E-Court E-Litigation: A Global Comparative Framework for Indonesia’s Electronic Civil Case Management System - Dian Latifiani; Baidhowi Baidhowi; Yustina Dhian Novita; Nur Arif Nugraha (Journal of Law and Legal Reform, 2026)
Recent changes to the judiciary in Indonesia have introduced digitalization of the country’s judicial system, including e-courts and e-litigation, aimed at improving efficiency and transparency. However, with the technological infrastructure still facing many issues and the absence of legal standards for digital information and system privacy, these e-court and e-litigations have not been successful thus far. This paper examines the judiciary’s digital presence and the structure of e-court systems in other countries to devise an ideal model for Indonesia’s electronic civil case management systems. The research employed normative, doctrinal, and comparative legal methodologies, primarily drawing on statutes, case law, and secondary literature. This paper supports 1) SDGs No. 16 on Peace, Justice and Resilient Institutions strengthening inclusive and peaceful societies for sustainable development, providing access to justice for all, 2) The seventh Asta Cita, which emphasizes a transparent, efficient, and accountable judicial system that strengthens legal certainty, accelerates digital transformation, and enhances equitable access to justice throughout Indonesia. The study indicates that an ideal model exists, comprising five key features: the ability to file electronically, pay court filing and service fees electronically, receive electronically served summons, attend court proceedings via telecommunications, and continuously improve human resources and digital legal education. The comparative research has identified particular strengths in different jurisdictions, such as the Netherlands in data protection, Australia in system interoperability, Norway and Spain in efficient procedural and system cybersecurity, Singapore and Malaysia in legal technology education, and the United Kingdom in user-friendly system design. The results of this research are pivotal for legal reforms in Indonesia. It presents actionable steps to modernize the judiciary, improve access to justice, and bolster public trust in the judiciary in the digital era. Additionally, the study outlines policies to assist Indonesia in incorporating the optimal elements of the jurisdictions analyzed to establish a comprehensive, transparent, and legally sustainable e-court system. The research is constrained by the absence of an empirical analysis of court system readiness and of the relatively shallow analysis of the developed technical system.